Globalisation and the mix of wage and profit taxes - Andreas Haufler; Alexander Klemm; Guttorm Schjelderup (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2006)
This paper analyses the development of the ratio of corporate taxes to wage taxes using a simple political economy model with internationally mobile and immobile firms. Among other results, our model predicts that countries reduce their corporate tax rate, relative to the wage tax, either when preferences for public goods increase or when a rising share of capital is employed in multinational firms. The predicted relationships are tested using panel data for 23 OECD countries for the period 1980 through 2001. The results of the empirical analysis support our central hypotheses.
urn:nbn:de:bvb:19-epub-885-5
Keywords: H20; H73; F15; F23; 330; capital and labour taxes; economic integration; multinational firms